Cytotoxic activity of broussochalcone a against colon and liver cancer cells by promoting destruction complex-independent β-catenin degradation. (September 2019) - Shin, Sora; Son, Younglim; Liu, Kwang-Hyeon; Kang, Wonku; Oh, Sangtaek
Abstract: Aberrant activation of β-catenin-response transcription (CRT) is a well-recognized characteristic of colorectal and liver cancers and thus a potential therapeutic target for these malignancies. Broussonetia papyrifera (paper mulberry) has been used as a herbal medicine to treat various diseases. Using a sensitive cell-based screening system, we identified broussochalcone A (BCA), a prenylated chalcone isolated from Broussonetia papyrifera, as an antagonist of CRT. BCA accelerated the turnover of intracellular β-catenin that was accompanied by its N-terminal phosphorylation at Ser33/37/Thr41 residues, marking it for ubiquitin-dependent proteasomal degradation. Pharmacological inhibition of glycogen synthase kinase-3β could not abrogate BCA-mediated degradation of β-catenin. BCA decreased the intracellular β-catenin levels in colon and liver cancer cells with mutations in β-catenin, adenomatous polyposis coli, and Axin. BCA repressed the expressions of cyclin D1, c-Myc, and Axin2, which are β-catenin/T-cell factor-dependent genes, and thus decreased the viability of colon and liver cancer cell. Moreover, apoptosis was elicited by BCA, as indicated by the increase in the population of Annexin V-FITC positive cells and caspase-3/7 activities in colon and liver cancer cells. These findings indicate that BCA exerts its cytotoxic effects by promoting phosphorylation/ubiquitin-dependent degradation of β-catenin and may potentially serve as a chemopreventive agent for colonrectal and liver cancers. Highlights: BCA is a specific antagonist of the Wnt/β-catenin pathway. BCA promotes β-catenin degradation protein via a destruction complex-independent mechanism. BCA represses β-catenin-dependent gene expression in colon and liver cancer cells. BCA decreases the viability of colon and liver cancer cells. BCA induces apoptosis in colon and liver cancer cells.